Examining Public Perceptions of Government Exploitation of National Emergencies - Patterson, Silas L. (Criminal justice and behavior, 2025)
The public expects governments to effectively respond to emergencies. These responses can raise concerns that governments are exploiting emergencies, consolidating power and infringing upon civil liberties. Despite these concerns, little research has explicitly examined perceptions that governments exploit emergencies or the possible correlates of these perceptions. Using a national sample of 600 American adults surveyed in the spring of 2020, and drawing from the legal socialization literature, we investigate: (a) the psychometric properties of a construct measuring perceptions of government exploitation during national emergencies, and (b) the correlates of these perceptions. Our findings indicate that these perceptions are distinct from other legal attitudes found in the legal socialization framework. These perceptions are significantly associated with distrust in government institutions, legal cynicism, and police legitimacy. We discuss policy implications and future research directions, highlighting the importance of these perceptions in effectively responding to national crises.